Business analysis - Paul, Debra; Cadle, James; Yeates, Donald (2014)
Includes the impact of Agile, an introduction to business architecture and expanded material on gap analysis and benefits management.
Includes bibliographical references and index.
oif 15/06/15
Loan
Keywords: Business planning; Business analysts; Strategic planning; System analysis; Management information systems; Organizational effectiveness